Toward a Political Economy Approach to Policy-based Lending - George Abonyi (Asian Development Bank (ADB), 2002)
"The paper identifies a set of core concepts that reflect key "political economy" factors shaping the policy reform process that can assist in guiding the policy-based lending (PBL) design process. It discusses the recurring themes that constrain the effectiveness of PBL, reviews from a political economy perspective the PBL experience at the Asian Development Bank (ADB) and elsewhere, and identifies some outstanding conceptual issues that would have to be tackled in the future in order to increase the likelihood of effective implementation of PBLs and to strengthen the joint capacity of developing member countries (DMCs) and ADB to design more effective PBL initiatives. While the problems traditionally encountered in PBL are unlikely to be eliminated in view of the nature of policy issues and reform, their frequency and intensity may perhaps be reduced if the domestic political economy context will be given proper recognition and accommodation in the PBL design process. It is also imperative to have a longer-time perspective since policy reform involves a process of change whose time horizon is likely to extend far beyond that of a particular PBL program."
hdl:11540/1929
Keywords: 330; Entwicklungsfinanzierung; Konditionalität; Wirtschaftsreform; Öffentliches Kreditprogramm; Entwicklungsländer; Asien